2020
DOI: 10.1371/journal.pone.0236278
|View full text |Cite
|
Sign up to set email alerts
|

A cointegration analysis of rabies cases and weather components in Davao City, Philippines from 2006 to 2017

Abstract: Rabies is a lethal viral disease and dogs are the major disease reservoir in the Philippines. Spatio-temporal variations in environmental factors are known to affect disease dynamics. Some rabies-affected countries considered investigating the role of weather components in driving rabies cases and it has helped them to strategize their control efforts. In this study, cointegration analysis was conducted between the monthly reported rabies cases and the weather components, such as temperature and precipitation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Since it is the country's largest city, cases were coming from 210 rabies-infected dogs documented from 2006 to 2017. Even though mass canine vaccination has been in place in Davao City since 2006, when other control measures impounding and neutering were implemented in 2011, rabies incidents continued to fluctuate [53]. Figure 4.…”
Section: Region-specific Morbidity and Mortality Ratesmentioning
confidence: 99%
“…Since it is the country's largest city, cases were coming from 210 rabies-infected dogs documented from 2006 to 2017. Even though mass canine vaccination has been in place in Davao City since 2006, when other control measures impounding and neutering were implemented in 2011, rabies incidents continued to fluctuate [53]. Figure 4.…”
Section: Region-specific Morbidity and Mortality Ratesmentioning
confidence: 99%
“…Several animal welfare organizations have already reported that incidences of dogs dying in hot cars are increasing ( British Veterinary Association 2019 ; Shih et al 2019 ). Increase in warm temperature also has an alarming correlation with an increase in dog bites ( Ahmed et al 2019 ) and rabies infections in dogs ( Lachica et al 2020 ). An increase in droughts may also worsen the rabies epidemic as rabies infection has been negatively correlated with precipitation ( Courtin et al 2000 ; Lachica et al 2020 ).…”
Section: Impact Of Climate Change On Companion Animalsmentioning
confidence: 99%
“…Increase in warm temperature also has an alarming correlation with an increase in dog bites ( Ahmed et al 2019 ) and rabies infections in dogs ( Lachica et al 2020 ). An increase in droughts may also worsen the rabies epidemic as rabies infection has been negatively correlated with precipitation ( Courtin et al 2000 ; Lachica et al 2020 ).…”
Section: Impact Of Climate Change On Companion Animalsmentioning
confidence: 99%
“…Despite this, there remains a need for a better understanding of how contact patterns and human mobility data translate into disease transmission dynamics (Klepac et al, 2018). The use of vaccination is one of the most effective and known strategy in making sure that infectious disease is controlled (Lachica et al, 2020;Vairo et al, 2017). Vaccination reduces the risk of disease transmission which essentially reduces the size of the susceptible population (Ibuka et al, 2016;Stier, Berman, & Bettencourt, 2020).…”
Section: Bt Analysis For Covid-19 Contagionmentioning
confidence: 99%